OPTIMISATION OF ARCHIVE MANAGEMENT AT THE PAOTERE MACASSAR MARITIME WEATHER STATION - Wahyuningsih, Sri; saiful, deni; Nasution, Irwansyah (Jurnal Widya Climago, 2023)
The National Archives of the Republic of Indonesia perform archival supervision of ministries / institutions and local governments in order to monitor the compliance of archiving implementation at each archive creator with archiving laws and regulations and to fulfill the assessment of the Quality of Records Management as measured by the Archival Supervision Score as stated in the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 26 of 2020 concerning Guidelines for Evaluating the Implementation of Bureaucratic Reform. The Makassar Paotere Maritime Meteorological Station received a sufficient category record based on the findings of an internal archive system audit carried out by the Meteorology, Climatology and Geophysics Agency in August 2021. This is because archive management has not been properly implemented in accordance with applicable regulations.